Contributions of the Extension Project “Strengthening and Expansion of the Obesity Care Line in the Public Health Network in Espírito Santo” to Curricular Integration - Ferreira, Ana Paula Ribeiro; Mello, Sanna Abigail de Jesus; Vasconcelos, Amanda Ferreira; Pieri, Isabella Lopes Del; Souza, Mariana Porto de; Souza, Sara da Silva; Gering, Sara Jarske (Guará Journal, 2025)
Obesity has shown high prevalence rates over recent years. This condition is associated with multiple factors and represents a major challenge for Brazil’s Unified Health System (SUS), requiring preventive measures, treatment strategies, and health education initiatives. In this context, the extension project “Strengthening and Expanding the Obesity Care Pathway in the Public Health Network of Espírito Santo” plays a fundamental role by contributing to the enhancement of healthcare services and the promotion of healthier lifestyles. This article aims to report the experience of this extension project, highlighting its impacts on academic training, the qualification of healthcare services, and community engagement. This is an experience report based on activities developed within the extension project. Information was collected through direct observation of the actions carried out and the documentation of project activities. The initiatives foster knowledge exchange among the university, healthcare professionals, and the community, providing students with valuable learning opportunities and practical experience, promoting continuing and high-quality professional development for healthcare workers, and facilitating access to information and health promotion activities for the community. It is concluded that curricular integration and the accreditation of extension activities play an essential role in preparing students and healthcare professionals to provide care for individuals with overweight and obesity.